Diagnostic module for the radiation beam system “TEMP-B” - Batrakov, A.B.; Glushko, E.G.; Yegorov, А.М.; Zinchenko, A.A.; Lonin, Y.F.; Ponomarev, A.G.; Fedotov, S.I. (Вопросы атомной науки и техники, 2017)
The power module designed for the calibration and adjustment of the units and components of microsecond accelerator of relativistic electron beams (REB) “Temp-B” has been developed and manufactured. The noise immune gauge of high charging voltages of the terminal capacitors used by four-channel pulse voltage generator (PVG) and the discharger operating in the broad band of charging voltages have been manufactured. The methods developed using the module and the manufactured noise immune gauge of high charging voltages were applied to the accelerator “Temp-B”. Разработан и изготовлен силовой модуль для калибровки и отладки узлов и элементов микросекундного ускорителя релятивистских электронных пучков (РЭП) “Темп-Б”. Изготовлены помехозащищённый измеритель высокого зарядного напряжения на оконечных конденсаторах четырёхканального генератора импульсного напряжения (ГИН) и разрядник, работающий в широком диапазоне зарядных напряжений. Разработанные на модуле методики и изготовленный помехозащищённый измеритель высокого зарядного напряжения применены на ускорителе “Темп-Б”. Розроблено та виготовлено силовий модуль для калібрування і налагодження вузлів та елементів мікросекундного прискорювача релятивістських електронних пучків (РЕП) “Темп-Б”. Виготовлено перешкодозахищений вимірювач високої зарядної напруги на кінцевих конденсаторах чотириканального генератора імпульсної напруги (ГІН) та розрядник, що працює в широкому діапазоні розрядних напруг. Розроблені на модулі методики і виготовлений перешкодозахищений вимірювач високої зарядної напруги застосовані на прискорювачі “Темп-Б”.